Analisis Perencanaan Sistem Informasi Tenaga Kerja Outsourcing Berbasis Web - Adam Imtiyaz; Khairul Anwar (Jurnal Rekayasa Proses dan Industri Terapan, 2023)
Seeing the existing constraints and the development of information technology which provides many conveniences, the authors provide useful thoughts for overcoming and minimizing these obstacles by implementing a web-based information system where work relations can request labor without having to come directly to the company or by telephone.